Membidik Masa Depan Bahasa Di Era Society 5.0; Kajian Pemertahanan Bahasa - Sofyaningrum, Rosita; Hidayah, Ningsih Lailatul (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2023)
The development of technology in the era of Society 5.0 has influenced social interactions and language changes. This research aims to describe the forms and functions of slang, as well as the importance of language maintenance that needs to be enhanced in the era of Society 5.0. The method used in this research is a qualitative descriptive method. This method describes language changes in terms of the formand function of slang, as well as the importance of language maintenance because of technological advancements in the era of Society 5.0. Data collection techniques were carried out through observation and note-taking. This method allows researchers to gain a deep understanding and insight that may not be visible through other approaches. Data was collected by observing language data used in digital platforms and then identifying them in the process of language formation and analysis of language functions.The results of this research include the existence of fifty slang words with the following formation processes: (1) phonemic structure reversal, (2) changes in the final syllable with -ay, (3) acronym, abbreviation, and phrase forms, (4) word reversal forms, and (5) words from regional languages. Data were analysed based on their functions as: (1) expressive, (2) directive, (3) informative, and (4) fative. As for research in the field of language maintenance resulting from technological changesand language usage, the required attitudes include: (1) language loyalty, (2) language pride, and (3) language norm awareness.